Primary follicular lymphoma of disguised as multiple miliary like lesions: A case report and review of literature - K Amita; M N Suma; S Vijay Shankar; C S Premalata; M Sanjay (Wolters Kluwer Medknow Publications, 2018)
Primary follicular lymphoma (PFL) of gastrointestinal tract (GIT) is rare and account for 1%-3% of non-Hodgkin lymphoma. Within the small intestine, the PFL is more common in jejunum than in the ileum. Due to low prevalence of the disease, the clinical manifestations are not well known, and diagnosis is usually delayed leading to complications. We herein report a case of PFL of GIT who presented with intestinal obstruction and unique gross morphology. Diagnosis was made by morphology and supported by immunohistochemistry.